A Novel WRKY Transcription Factor, MuWRKY3 (Macrotyloma uniflorum Lam. Verdc.) Enhances Drought Stress Tolerance in Transgenic Groundnut (Arachis hypogaea L.) Plants - Kiranmai, Kurnool; Lokanadha Rao, Gunupuru; Pandurangaiah, Merum; Nareshkumar, Ambekar; Amaranatha Reddy, Vennapusa; Lokesh, Uppala; Venkatesh, Boya; Anthony Johnson, A. M.; Sudhakar, Chinta (Frontiers in Plant Science, 2018)
Drought stress has adverse effects on growth, water relations, photosynthesis and yield of groundnut. WRKY transcription factors (TFs) are the plant-specific TFs which regulate several down-stream stress-responsive genes and play an essential role in plant biotic and abiotic stress responses. We found that WRKY3 gene is highly up-regulated under drought stress conditions and therefore isolated a new WRKY3TF gene from a drought-adapted horsegram (Macrotyloma uniflorum Lam. Verdc.). Conserved domain studies revealed that protein encoded by this gene contains highly conserved regions of two WRKY domains and two C2H2 zinc-finger motifs. The fusion protein localization studies of transient MuWRKY3-YFP revealed its nuclear localization. Overexpression of MuWRKY3 TF gene in groundnut (Arachis hypogaea L.) showed increased tolerance to drought stress compared to wild-type (WT) plants. MuWRKY3 groundnut transgenics displayed lesser and delayed wilting symptoms than WT plants after 10-days of drought stress imposition. The transgenic groundnut plants expressing MuWRKY3 showed less accumulation of malondialdehyde, hydrogen peroxide (H2O2), and superoxide anion (O2●− ), accompanied by more free proline, total soluble sugar content, and activities of antioxidant enzymes than WT plants under drought stress. Moreover, a series of stress-related LEA, HSP, MIPS, APX, SOD and CAT genes found up-regulated in the transgenic groundnut plants. The study demonstrates that nuclear-localized MuWRKY3 TF regulates the expression of stress-responsive genes and the activity of ROS scavenging enzymes which results in improved drought tolerance in groundnut. We conclude that MuWRKY3 may serve as a new putative candidate gene for the improvement of stress resistance in plants.